MLVA as an Epidemiological Tool To Trace Back Brucella melitensis Biovar 1 Re‐Emergence in Italy. Issue 5 (21st July 2015) - De Massis, F.; Ancora, M.; Atzeni, M.; Rolesu, S.; Bandino, E.; Danzetta, M. L.; Zilli, K.; Di Giannatale, E.; Scacchia, M.
Summary Brucellosis is an important zoonosis caused by Brucella spp., still prevalent in most areas of the world. Brucellosis control in animals is the key to protect humans. The knowledge of Brucella spp. prevailing genotypes in a territory represents an important epidemiological tool to formulate policies and strategies for disease control and to trace back the introduction of new strains previously considered as exotic. In the last years, multiple‐locus variable number tandem repeat analysis (MLVA) has been proposed as complementary to classical biotyping methods. MLVA may add important information to the classical epidemiological investigation techniques, to help in tracing back sources of infection in brucellosis outbreaks. Sardinia is an Italian region officially free from sheep and goats brucellosis since 1998. In 2011, Brucella melitensis biovar 1, a biotype not reported in Italy since 1995, was isolated in one flock in the region. The genotyping MLVA‐16 showed that isolates belonged to a rare American lineage, confirming it was introduced from other countries. The strain was considered as probably originating from Spain, where this lineage is endemic. BrucellaMLVA‐16 has been proved to be useful to analyse the epidemiological correlation of strains enabling to trace its geographic origin by comparing their previously reported genetic patterns.